A response adaptive design for ordinal categorical responses. Issue 6 (2nd November 2018) - Biswas, Atanu; Bhattacharya, Rahul; Das, Soumyadeep
ABSTRACT: A two treatment response adaptive design is developed for phase III clinical trials with ordinal categorical treatment outcome using Goodman-Kruskal measure of association. Properties of the proposed design are studied both empirically and theoretically and the acceptability is further illustrated using two real data-sets; one from a clinical trial with trauma patients and the other from a trial with patients having rheumatoid arthritis.